ANALISIS AKUNTABILITAS PEMERINTAH DESA KARANGREJO DALAM MENGELOLA ALOKASI DANA DESA (ADD) - Pratiwi, Aprilia Diah; Sholihin, Ustadus; Ali, Muhammad Mahbubi (Commodities, Journal of Economic and Business, 2022)
A company expects maximum productivity results from its employees. But sometimes there are some things that can reduce the quality of an employee's performance such as the effect of safety given and health that is given. If left unchecked for sure productivity in the company will not be effective and efficient so that it can result in a decrease in company quality and reduce corporate profits. With the formulation of the problem whether there is an influence between occupational safety and health on productivity simultaneously or partially. By knowing this relationship, the Lirboyo Kediri General Hospital can predict the next step in making decisions and can improve occupational safety and health for its employees. The variables in this study consisted of occupational safety (x1), occupational health (x2), while the variable affected was productivity (y) with the sampling technique was simple random sampling, ie the technique of taking sample members from the population was done randomly without regard to existing strata in that population. Data obtained through questionnaires, interviews and observations. The results of the analysis conducted showed that occupational safety and health on the productivity of employees has a correlation of r of 0.760 or 76.0%, which means that the magnitude of the correlation is close to 100%.